Development of Interactive PowerPoint Based Learning Media in Overcoming Social Anxiety of MTs Ma'arif Jumo Students When Public Speaking - Anita, Nesya Ayu; Venty, Venty; Widiharto, Chr. Argo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: this study aims to overcome students' anxiety when speaking in public MTs grade 7 student Ma'arif Jumo. In addition, this study also aims to determine the effectiveness of the results of the development of Interactive PPT-based learning media on social anxiety material at MTs Ma'arif Jumo.This study uses an RnD approach (research and Development). The focus in this study is research on the development of interactive PPT-based learning media in overcoming the anxiety of MTs Ma'arif Jumo students when speaking in public. The development model is in the form of the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). Based on the calculation of the hypothesis test, the results were gnified (2-tailed) 0.000 0.05. Thus, there is a significant difference between the initial variable (ore-test) and the final variable (post-test). Thus, Ho is rejected and Ha is accepted. On the basis of these calculations, the alternative hypothesis (Ha) which reads